Efektivitas prinsip relevansi dalam program mentoring BTAQ terhadap kemampuan baca Al-Qur’an peserta didik - Muhammad Raja Iqbal Fahri; Mohamad Erihadiana; Asep Nursobah (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2026)
This study investigates the effectiveness of implementing the principle of relevance in the BTAQ (Baca Tulis Al-Qur'an) mentoring program at SMP PGII 1 Bandung in improving students' Qur'an reading skills. The study employed a mixed-methods approach using an explanatory sequential design. Quantitative data were collected through pretest and posttest assessments of students' Qur'an reading abilities, while qualitative data were obtained through interviews and observations to further explain the quantitative findings. The quantitative results, analyzed using a paired-samples t-test, revealed a statistically significant difference between pretest and posttest scores (p = 0.017, p < 0.05), indicating that the implementation of the BTAQ mentoring program effectively improved students' Qur'an reading skills. The qualitative findings further demonstrated that the program aligned with students' learning needs, the school's vision and mission, and contemporary social challenges. These findings suggest that integrating the principle of relevance into BTAQ mentoring programs can enhance students' Qur'an reading competencies and may serve as a model for developing relevant and effective Islamic education curricula.